2021
DOI: 10.1007/s11356-021-16787-x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal, physical, mechanical and microstructural properties of dredged sediment-based ceramic tiles as substituent of kaolin

Abstract: The aim of this study was to recycle dredged sediments as an alternative raw material in the production of ceramic tiles. The effect of the substitution of kaolin by raw sediment (HDS) and calcined sediment (HDSC) in the mixture of the ceramic tile samples sintered at 1100 and 1200 °C was studied. The samples were prepared with different proportions of HDS and HDSC (0, 10, 20 and 30 wt.%) substituting kaolin. The mineralogical analysis of the samples shows that mullite phase disappears in the samples incorpora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Only the TF clay test tiles with CuFe 2 O 4 and Fe 3 O 4 nanoparticle additions showed an increase in flexural strength up to 9% and 16%, respectively, at 1% ( w / w ) compared with the 0% ( w / w ) mixture. The low water absorption (2.8% and 2.5%) at 1% ( w / w ) magnetite nanoparticles indicate a higher density of the test tile and, consequently, a higher flexural strength (1787 N) promoted by the formation of a crystalline and liquid-phase developed at low-temperature associated with the iron oxide content [ 73 , 74 , 75 ]. Test tiles with the addition of Ag 2 O and SiO 2 nanoparticles decreased the flexural strength by 13–16% and 1–5%, respectively, at 1% and 5% ( w / w ), compared at 0% mixture.…”
Section: Resultsmentioning
confidence: 99%
“…Only the TF clay test tiles with CuFe 2 O 4 and Fe 3 O 4 nanoparticle additions showed an increase in flexural strength up to 9% and 16%, respectively, at 1% ( w / w ) compared with the 0% ( w / w ) mixture. The low water absorption (2.8% and 2.5%) at 1% ( w / w ) magnetite nanoparticles indicate a higher density of the test tile and, consequently, a higher flexural strength (1787 N) promoted by the formation of a crystalline and liquid-phase developed at low-temperature associated with the iron oxide content [ 73 , 74 , 75 ]. Test tiles with the addition of Ag 2 O and SiO 2 nanoparticles decreased the flexural strength by 13–16% and 1–5%, respectively, at 1% and 5% ( w / w ), compared at 0% mixture.…”
Section: Resultsmentioning
confidence: 99%
“…Measuring the stability of suspensions and thus determining the sedimentation rate is a way to calculate the average grain diameter of ceramic powder. The rate of particle fall is affected by factors such as ambient temperature, medium viscosity and grain size [51]. The measurement was carried out for a 0.5 g powder sample suspended in distilled water at 23 • C (water density 997.66 kg/m 3 ).…”
Section: Determination Of Average Grain Diametermentioning
confidence: 99%
“…The large production volumes make this a resource-intensive industry (Appolloni et al 2022;Atılgan Türkmen et al 2021) as shown by the specific consumption of production factors, which are on average: raw materials 20÷21 kg/m 2 , water 0.2÷0.3 m 3 / m 2 , electricity 6÷7 kWh/m 2 , methane gas 3÷4 Sm 3 /m 2 . The intensive use of resources (Slimanou et al 2021) and the complex system of transport of large masses of raw materials (sourcing) and finished product (distribution) that characterize this industry, generate multiple environmental loads along the supply chain, making this context very promising for the validation of O-LCA in an operational setting.…”
Section: Context Of Applicationmentioning
confidence: 99%